Substrate recognition and function of the R2TP complex in response to cellular stress - von Morgen, Patrick; Hořejší, Zuzana; Macurek, Libor (Frontiers in Genetics, 2015)
The R2TP complex is a HSP90 co-chaperone, which consists of four subunits: PIH1D1, RPAP3, RUVBL1, and RUVBL2. It is involved in the assembly of large protein or protein–RNA complexes such as RNA polymerase, small nucleolar ribonucleoproteins (snoRNPs), phosphatidylinositol 3 kinase-related kinases (PIKKs), and their complexes. While RPAP3 has a HSP90 binding domain and the RUVBLs comprise ATPase activities important for R2TP functions, PIH1D1 contains a PIH-N domain that specifically recognizes phosphorylated substrates of the R2TP complex. In this review we provide an overview of the current knowledge of the R2TP complex with the focus on the recently identified structural and mechanistic features of the R2TP complex functions. We also discuss the way R2TP regulates cellular response to stress caused by low levels of nutrients or by DNA damage and its possible exploitation as a target for anti-cancer therapy.